Menyoal Agapisme Klasik di Indonesia : Sebuah Dialektika Mengenai Anders Nygren dan Apropriasi Terhadap Eros dalam Etika - Abel Kristofel Aruan (Indonesian Journal of Theology, 2019)
In Indonesia, the discussion concerning the meta-ethical basis for the doing of good to others is still dominated by agapism, which is the line of thought claiming that agape is the highest form of love, done by God, and that which is proper for a Christian to bear out. Theological refutations have begun to emerge there, from theologians such as Ferry Mamahit and Joas Adiprasetya. Mamahit criticizes the dichotomous polarization of agape apart from eros, while Adiprasetya restores the goodness of philia vis-à-vis agape. This essay criticizes agapism, especially the classical agapism of Anders Nygren, from an overtly philosophical angle. With assistance from the philosophical anthropological apparatus of Christian thinker James K. A. Smith, I explicate how desire (erotic-love) is an inherent quality of being human. The problem does not lie in whether humankind should want to jettison eros—which is the normative prescription of Nygren—because eros is the ultimate impulse that in actuality underlies good deeds toward others. The issue lies precisely in what is to be the final purpose (causa finalis) of any good deed. To complement Smith’s thought, this essay employs Nicholas Wolterstorff’s proposal that shalom serve as the causa finalis of a person’s doing good. The intent of all this effort is to underscore that the Smith/Wolterstorff model is more in line with reality than is agapism.